Serum Total Bilirubin and Progression of Chronic Kidney Disease and Mortality: A Systematic Review and Meta-Analysis - Li, Jia; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Medicine, 2021)
Background: Previous studies have suggested that serum total bilirubin (STB) levels are associated with heightened chronic kidney disease (CKD) and mortality in both the general population and nephropathy patients. However, these results remain inconsistent. The aim of our study was to investigate whether STB was a predictor for progression of CKD and mortality by meta-analysis. Methods: We performed a systematic literature search in PubMed, Web of Science, MEDLINE, EMBASE, Google scholar and Cochrane Library database up to June 30, 2019. Pooled risk ratios (RR) and corresponding 95% confidence intervals (CI) were extracted for the highest vs. lowest category STB levels within the physiological range, and a random-effects model was applied to calculate the dose–response relationships. A pooled hazard ratio (HR) was used to investigate the association between STB levels and mortality in dialysis patients. Results: A total of 16 studies followed from 21 months to 7 years were eligible for inclusion in the study. For the categorized STB, 11 studies with 41,188 participants were identified and analyzed. Patients with the highest STB levels were associated with a lower risk of CKD (RR=0.64; 95% CI 0.55–0.73) compared to those with the lowest STB levels. Furthermore, based on 7 studies, a pooled RR of 0.89, 95%CI (0.80-0.99) was observed for the continuous STB levels (per 0.2 mg/dL increase). 4 studies that included 51,764 participants illustrated that there was no association between the STB levels and all-cause mortality (HR=0.77; 95%CI 0.42–1.41). A prominent negative linear relationship (𝜒2 = 14.70; P = 0.0001) was found between STB levels and risk of CKD. Subgroup analyses showed that there were no significant differences in the subgroup adjustment factor except for sample size. Conclusions: Elevated STB levels within a physiological range are associated with lower risk of CKD regardless of the study characteristics, and coincided with a liner dose–response relationship. However, whether high STB levels are a protective factor against mortality remains inconclusive. Large-scale randomized controlled trials are needed to target STB levels for predicting renal outcomes.